Faktor-Faktor yang Berhubungan dengan Pengelolaan Sampah Rumah Tangga di Wilayah Kerja Puskesmas Pakue Kecamatan Pakue Kabupaten Kolaka Utara Faktor-Faktor Yang Berhubungan Dengan Pengelolaan Sampah Rumah Tangga Di Wilayah Kerja Puskesmas Pakue Kecamatan Pakue Kabupaten Kolaka Utara - Nurhana; Rahmawati Azis; Asrijun Juhanto (2022)
Garbage is an object or material that is no longer used by humans and is finally thrown away. The public's view of this waste is defined as something dirty, slum and so on that must be burned or thrown away. The purpose of the study was to determine the factors related to household waste management in the work area of ​​the Pakue Health Center, Pakue District, North Kolaka Regency. This research was conducted in the work area of ​​the Pakue Health Center, Pakue District, North Kolaka Regency. The type of research used is analytic survey research with a “cross-sectional” approach, where all observed variables are measured simultaneously when the research takes place. The results obtained that there is a relationship between knowledge and household waste management with p value = 0.000 < = 0.05, There is a relationship between attitude and household waste management with p value = 0.000 < = 0.05, There is a relationship between facilities and household waste management with p value = 0.000 < = 0.05 and multivariate analysis of the most dominant variable is the means with an Exp (B) or OR value of 14,813. Suggestions for research are that community empowerment efforts are needed that can increase community knowledge and interest in waste management, socialization or counseling carried out by health workers regarding household waste management so that they can increase public awareness or attitudes in good behavior regarding waste management and facilities and infrastructure are needed. that meet the health standards available at TPS locations so as not to interfere with community activities.